Optimizing the extraction of phenolic compounds from Bixa orellana L. and effect of physicochemical conditions on its antioxidant activity (2014)
ABSTRACT: For this work, the surface response methodology was applied in order to optimize the extraction using solvents of phenolic compounds present in Bixa orellana L. seeds through a central composite design that evaluated the effect of the factors: extraction time (36 to 60 h) and the solvent ml/g seed ratio (2/1 to 4/1), for the response variable total phenol content extracted from the seed. The levels on the factors that maximized the response variable were: extraction time of 60 h, and the solvent/seed ratio of 4 ml/g. For the extracts obtained at these conditions the effect of pH, and the solid content was evaluated for the antioxidant activity and the total phenols content. The results in this case showed that for higher pH values, the content of total phenols increased as well as the antioxidant activity, being a pH of 6.67 and solid content of 13.62°Brix, the optimal conditions for these variables.